Optimizing instagram as a supporting platform for self-taught arabic learning for islamic boarding school students - Anggia Rita Andriana; Nanda Pratama; Siti Qomala Khayati; Musa Zulkifli; Nimuhammadfatin Samae; Muhammad Shalahuddin Al Awwaby (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research aims to optimize the use of Instagram as a supportive platform in self-directed Arabic language learning for students at Islamic boarding schools. Through the use of a qualitative case study-based method, this research measures the researchers by analyzing relevant articles on the use of Instagram in Arabic language learning. Data were collected through observation, interviews, documentation, and content analysis of online articles. The research results show that Instagram can enhance learning motivation, enrich vocabulary, and facilitate the understanding of Arabic grammar through interactive content in the form of videos, texts, and images. Additionally, Instagram provides a more engaging and contextual learning experience outside the formal classroom. This research recommends optimizing Instagram features to support self-directed Arabic language learning and encourages lecturers and students to be more creative in utilizing social media as an educational tool in the digital era.